Behavioral Interaction of Male and Female Canaries (Serinus canaria) During the Reproduction Period - Nugroho, Anwari Adi; Nur'Aini, Citra Aisyah; Asy-syifaiyah, Asma'; Septianingrum, Parigi Akhiri (Universitas Muhammadiyah Surakarta, 2025)
The study aimed to describe the interaction between male and female bird canary (Serinus canaria ) during reproduction. Study This uses the ad libitum sampling method, namely observing activity act in demand bird canary male and female (Serinus canaria) during mating. Study This was done 6 days on Sunday, the first (2 days) introduction bird canary, and Sunday, the second and third (4 days) matchmaking bird canary. Research results show various Acts in demand reproduction of bird canaries during mating. Observation results show that bird canary males use tweets and appearances and physiques for interesting attention female, temporary females choose partners based on tweets male and mark fitness other. After the introduction process, birds canary mated males and females​ collaborate in the guard nest and raise children. The study still has limitations on the relative sample​ , as it only uses two pairs of bird walnuts and the duration of the observations​ is limited to three Sundays. This matter does not fully represent all the variations in existing behavior​ in the population of bird canaries. Apart from that, the factors influencing the environment and conditions and other specific aspects of on-site research must also be considered when interpreting results.